FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN TOILET TRAINING PADA ANAK USIA 3-5 TAHUN DI PAUD SE-KOTA PEKANBARU TAHUN 2017 - M.Dedi Widodo, Sherly Vermita Warlenda, Riri Maharani, (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Toilet training in children is an attempt to train children to be able to control theconduct of urination and defecation. Toilet training can take place on the stages of life ofchildren, ages 18 months-2 years. In doing exercise urination and greater in childrenrequires preparation both physically, psychologically and intellectually, through thepreparation of the expected child is able to control bowel or small individually.This type ofresearch is analytic with cross sectional approach. The sample in this study were 250respondents in early childhood Cerliana Islam. The sampling technique using samplingtechniques random. The data collection was conducted using questionnaires, data analysisunivariate and bivariate.The results were tested statistically by chi square test at 95%confidence level using computer program. The results showed. There is a significantcorrelation between mother's knowledge with toilet training (Pvalue = 0,001 <a (0,05)),and there is no significant correlation between maternal education with toilet training in3-5 year olds (Pvalue = 0.07 <a (0,05)), and there is correlation to Patterns of Custodywith the implementation of toilet training in children aged 3-5 years (Pvalue = 0.001 <a(0,05)) in PAUD Se-Town Pekanbaru Year 2017.It is expected that mothers should beexpected to inform mothers about the implementation of toilet training and provide insightinto the implementation of toilet training and the benefits of toilet training with regard tochild self-reliance.Keywords : Knowledge, Education, ImplementationToilet Training.